Pengaruh Bullions Bank, Volatilitas Emas Global, kebijakan Moneter Indonesia terhadap Investasi Emas di Bank Syariah Indonesia - Ogi Marsenal Ipando; Ahmad Habibi; Muhammad Iqbal Fasa (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to investigate the relationship between global gold market dynamics—specifically Bullion Bank activities and gold price volatility and Indonesia's domestic monetary policy on gold investment behavior at Bank Syariah Indonesia (BSI) between January 2023 and November 2025. Employing descriptive quantitative analysis, the findings reveal a significant collective influence of these three external factors on customer interest in gold investment. The model effectively accounts for 82.5% of the variation in investment interest, highlighting the crucial role of global market sentiment and national macroeconomic directives in shaping gold investment decisions. Interestingly, separate analyses indicate that both Bullion Bank activities and global gold price volatility have a positive and significant impact. Gold investors at BSI tend to leverage price fluctuations for short-term speculative gains, rather than viewing gold purely as a safe-haven asset. Conversely, a rise in Bank Indonesia's benchmark interest rate (BI Rate) also shows a positive and significant effect on gold investment interest, reinforcing the principle of opportunity cost, where fixed-income financial instruments become more appealing during periods of high interest rates. The practical implications of this research underscore the need for BSI to develop adaptive strategies for market risk management, and for regulators, the importance of maintaining stable macroeconomic policies.